The influence of spectral composition on spring and autumn phenology in trees. (15th May 2019) - Brelsford, Craig C; Nybakken, Line; Kotilainen, Titta K; Robson, T Matthew
Abstract: Several recent reviews highlight the molecular mechanisms that underpin phenological responses to temperature and photoperiod; however, these have mostly overlooked the influence of solar radiation and its spectral composition on these processes. For instance, solar radiation in the blue and ultraviolet (UV) regions of the spectrum, as well as the red/far-red (R:FR) ratio, can influence spring and autumn phenology. Solar radiation reaching the Earth changes diurnally and seasonally; however, rising global temperatures, latitudinal range shifts and light pollution are likely to produce novel combinations of phenological cues for tree species. Here, we review the literature on phenological responses to spectral composition. Our objective was to explore the natural variation in spectral composition using radiative transfer models and to reveal any species-specific or ecotype-specific responses relating to latitudinal origin. These responses are likely to be most pronounced at high latitudes where spectral composition varies most throughout the year. For instance, trees from high latitudes tend to be more sensitive to changes in R:FR than those from low latitudes. The effects of blue light and UV radiation on phenology have not been studied as much as those of R:FR, but the limited results available suggest both could be candidate cues affecting autumn leaf colouration and senescence. Failure of more–southern species and ecotypes to adapt and use spectral cues during northwards range shifts could result in mistimed phenology, potentially resulting in frost damage, reduced fitness and limited range expansion. Future areas for research should look to establish how consistently different functional types of tree respond to spectral cues and identify photoreceptor-mediated mechanisms that allow plants to combine information from multiple light cues to coordinate the timing of phenological events. It should then be feasible to consider the synchronous or sequential action of light cues within a hierarchy of environmental factors regulating phenology.